ANALISIS PRODUK UNGGULAN DAERAH KOTA SALATIGA TAHUN 2020 - Teguh Pamuji Tri Nur H; Is Solikhatun (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2021)
This research were aims to see what commodities can become regional superiors in SalatigaRegency, so that they are able to make a high contribution to the economy of Salatiga Regency. Itis hoped that by knowing the superior potential, the right policies for regional economicdevelopment can be identified based on regional potentials. The results of this study, whichbecame the leading commodities were: enting gepuk, lung chips, brown rice and black rice drinks,upcycle tire crafts, D-9 cassava cheese, Plumpungan Batik, Selotigo Batik, handicrafts from flour(clay), and education station.